2003
DOI: 10.1177/039463200301600310
|View full text |Cite
|
Sign up to set email alerts
|

Different Cytokine Production and Effector/Memory Dynamics of αβ+ or γδ+ T-Cell Subsets in the Peripheral Blood of Patients with Active Pulmonary Tuberculosis

Abstract: Immunity to M.tuberculosis (MTB) infection consists of interactions between various T-cell subsets that control the infection and prevent further reactivation. We analysed the effector/memory T-cell dynamics and cytokines production in the peripheral blood of patients with pulmonary tuberculosis (TB). We observed that the frequency of CD4+ T-cell effectors was significantly increased during active TB, confirming a major role of this T-cell subset in TB immunity. Pre-terminally differentiated CD8+ T-lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…The evidence of IL-6 as the major growth factor for myeloma cells is supported primarily by the observation of enhanced proliferative activity induced by IL-6 in short term cultures (20,(38)(39)(40). In our study, high levels ofIL-6 were associated with proliferative activity as assessed by the PCNA ofbone marrow plasma cells in pretreatment patients.…”
Section: Discussionsupporting
confidence: 63%
“…The evidence of IL-6 as the major growth factor for myeloma cells is supported primarily by the observation of enhanced proliferative activity induced by IL-6 in short term cultures (20,(38)(39)(40). In our study, high levels ofIL-6 were associated with proliferative activity as assessed by the PCNA ofbone marrow plasma cells in pretreatment patients.…”
Section: Discussionsupporting
confidence: 63%
“…71,72 A cd response to ESAT-6 was also observed in patients with active pulmonary tuberculosis. 73 Others reported that ESAT-6 directly induces purified cd T effector memory cells from tuberculin skin testpositive patients to produce IFN-c, and that CD4 1 ab T cells regulate this response. 74 However, this observation has been challenged and it requires further investigation.…”
Section: Soluble Proteinsmentioning
confidence: 99%
“…In contrast to acute systemic infections such as malaria, in tuberculosis (TB) the number and function of Vd2 + T cells are downregulated. [19][20][21][22] A variety of mechanisms have been proposed for the decrease in Vd2 + T-cell function in TB, including redistribution to the lung parenchyma, lack of CD4 + T helper activity, activation-induced cell death and immune suppression. 14,23 Regulatory T cells (Tregs) have a major role in suppressing other immune cells such as CD4…”
Section: Vd2mentioning
confidence: 99%